2010
DOI: 10.1121/1.3455831
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular evoked myogenic responses to amplitude modulated sounds

Abstract: Auditory steady state responses (ASSR) allow objective assessment of hearing thresholds. At high stimulation levels artifactual responses have been reported in subjects with severe to profound deafness. Relatively large amplitude 'steady state' responses to amplitude modulated tones were measured from the Sternocleidomastoid muscle at 500 Hz. Response thresholds were similar to those of vestibular evoked myogenic potentials and scaled with neck muscle tension. 'Steady-state' myogenic responses showed broad tun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 12 publications
7
19
0
Order By: Relevance
“…oVEMP was recorded using click, 500 Hz short duration tone burst, and 500 Hz mixed amplitude modulated stimuli. Best cVEMP response using a frequency modulation of 39 Hz with 100% amplitude modulation and 10% of frequency modulation depth at 500 Hz short duration tone burst was obtained [14] (see Table 1). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…oVEMP was recorded using click, 500 Hz short duration tone burst, and 500 Hz mixed amplitude modulated stimuli. Best cVEMP response using a frequency modulation of 39 Hz with 100% amplitude modulation and 10% of frequency modulation depth at 500 Hz short duration tone burst was obtained [14] (see Table 1). …”
Section: Methodsmentioning
confidence: 99%
“…At the same time, no difference between the two stimuli with regards to response latency or amplitude was obtained [13]. In addition, higher amplitude responses were seen over a range of modulation frequencies (5, 39, 59, 78, 98, and 122 Hz), and specifically the 39 Hz modulation frequency yielded the largest amplitude response [14]. …”
Section: Introductionmentioning
confidence: 99%
“…Thus, the ability of airborne infrasound to elicit VEMPs has yet to be tested, and we attempted this for cVEMPs using continuous tones. Two previous studies 8,9 showed that vestibular responses can be elicited with continuous acoustic stimulation. They utilized SAM of midfrequency carriers (250-1000 Hz) with infrasonic and low-frequency modulation rates .…”
Section: Introductionmentioning
confidence: 98%
“…Because of this, recent studies have tested alternative types of stimuli, such as low-frequency tone bursts 7 and continuous tonal stimulation with sinusoidal amplitude modulation (SAM) at low rates. 8,9 In this work, infrasound (f < 20 Hz) was tested as an additional alternative, because vestibular receptor cells 10 and the entire vestibular system 11,12 are most responsive to mechanical vibration at very low frequencies. Also, as the transport of acoustic energy from the oval window to the otolith hair cells is impeded by fluid inertia, an effect that declines towards lower frequencies with 6 dB/octave, it might be expected that more acoustic energy reaches the otoliths at low frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…This is a much faster and more accurate test, in terms of compromised frequencies (11) . Studies conducted on the use of the steady-state technique to detect the VEMP found that this test, as well as auditory evoked potential, can also be performed in the frequency domain (7,12) . In addition to early detection of inferior vestibular nerve disorders, it favors a more accurate diagnosis in a shorter time frame and independent of the examiner's interpretation (7) .…”
Section: Introductionmentioning
confidence: 99%